Common and Distinct Disruptions of Cortical Surface Morphology Between Autism Spectrum Disorder Children With and Without SHANK3 Deficiency - Li, Dongyun; Liu, Chunxue; Huang, Ziyi; Li, Huiping; Xu, Qiong; Zhou, Bingrui; Hu, Chunchun; Zhang, Ying; Wang, Yi; Nie, Jingxin; Qiao, Zhongwei; Yin, Dazhi; et al. (Frontiers in Neuroscience, 2021)
SHANK3 caused autism spectrum disorder (ASD) may present a unique opportunity to clarify the heterogeneous neuropathological mechanisms of ASD. However, it remains largely unknown the specificity and commonality of disrupted large-scale brain organization in SHANK3 deficient children. The present study combined genetic tests, neurobehavioral evaluations, and magnetic resonance imaging, aiming to explore the disruptions of both local and networked cortical structural organization in ASD children with and without SHANK3 deficiency. Multiple surface morphological parameters such as cortical thickness and sulcus depth were estimated, and graph theory was adopted to characterize the topological properties of structural covariance networks (SCNs). Finally, correlation analysis between the alterations in brain morphological features and the neurobehavioral evaluations was performed. Compared with typically developed children, increased cortical thickness and reduced nodal degree were found in both ASD children with and without SHANK3 defects mainly in the lateral temporal, prefrontal cortex (PFC), temporo-parietal junction (TPJ), superior temporal gyrus (STG) and limbic/paralimbic regions. Besides commonality, our findings showed some distinct abnormalities in ASD children with SHANK3 defects compared to those without. Locally, more changes in STG and orbitofrontal cortex were exhibited in ASD children with SHANK3 defects, while more changes in TPJ and inferior parietal lobe in those without SHANK3 defects. For the SCNs, a trend towards regular network topology was observed in ASD children with SHANK3 defects, but not in those without. In addition, ASD children with SHANK3 defects showed more alterations of nodal degrees in anterior and posterior cingulate cortex and right insular, while more disruptions in the sensorimotor areas, the left insular and dorsomedial PFC in ASD without SHANK3 defects. Our findings indicate dissociable disruptions of local and networked brain morphological features in ASD children with and without SHANK3 deficiency. Moreover, this monogenic study may provide a valuable path for parsing the heterogeneity of brain disturbances in ASD.